PEMETAAN TOPIK NILAI PUBLIK DALAM PENELITIAN - Wulandari, Rika; Rochima, Emma; Rianto, Yan; Endyana, Cipta (BACA: Jurnal Dokumentasi dan Informasi, 2020)
This study aims to provide an overview of how public value research topics developed from 2001 to 2020. The mapping is expected to provide an overview of the development of research and provide input on the topic of public value research. This study uses the Scopus database from 2001 to 2020 to calculate citation analysis using the Publish or Perish (PoP) application and mapping publications using the VOSViewer application. From the analysis of literature studies based on the Scopus database from 2001 to 2020 272 journal articles are discussing public value research, it was found that the most publications were in 2019 (47 publications) and the highest research was dominated by the United Kingdom (65). For the highest number of citations, the publication with the title "From new public management to public value: Paradigmatic change and managerial implications" was 368 citations. Social science subjects are the most discussed in research on public values. The results of the visualization with the VOSViewer application for a public value research network visualization map are divided into 4 clusters. Density visualization maps can be seen that research on the topic of public value with the subject of performance management and cultural policy is still small, so there is still a chance for research. Based on the analysis of the research topic of public value, there is still a large enough opportunity for research to be carried out, especially in Indonesia based on the Scopus database, researchers have not researched the topic of public value research.